The Economic, Social and Political Elements of Climate Change - Leal Filho, Walter (Climate Change Management, 1610-2010, 2011)
A unique feature of this book is its strong practice-oriented nature: it contains a wide range of papers dealing with the social, economic and political aspects of climate change, exemplifying the diversity of approaches to climate change management taking place all over the world, in a way never seen before. In addition, the book describes a number of projects and other initiatives happening in Africa, Asia, Europe, Latin American and the Australasian region, providing a profile of the diversity of works taking place today.(P)